Hydroxypropylmethyl cellulose (HPMC) crosslinked keratin/hydroxyapatite (HA) scaffold fabrication, characterization and in vitro biocompatibility assessment as a bone graft for alveolar bone regeneration - Sandleen Feroz (Elsevier, 2021)
Wool derived keratin has garnered significant advancements in the field of biomaterials for hard tissue regeneration. The main limitation of keratin-based biomaterials for bone tissue engineering is their fragile nature. This paper proposes the development of a novel hydroxypropyl methylcellulose (HPMC) crosslinked keratin scaffold, containing hydroxyapatite as a major inorganic component by freeze drying technique for alveolar bone regeneration. The prepared keratin/hydroxyapatite/HPMC (K/HA/HPMC) scaffold was characterized to study its chemical, physical, and mechanical properties by Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), Energy dispersive X-ray spectroscopy (EDX), X-Ray diffractometric (XRD) analysis. The SEM images of the scaffolds showed highly porous interconnected architecture with average pore size of 108.36 ± 22.56 while microcomputed tomographic analysis measured total porosity as 79.65 %±. Energy dispersive X-ray spectroscopic (EDX) analysis confirmed that inorganic component of scaffold was mainly composed of calcium and phosphorous ions having Ca/P molar ration of 1.6. The maximum compressive strength was found to be in the range of 0.841 ± 0.37 MPa. Furthermore, the K/HA/HPMC scaffold was structurally stable and weight loss of about 26% was observed when soaked in phosphate buffered solution (PBS) for 28 days. In vitro biocompatibility testing showed that K/HA/HPMC scaffold was cytocompatible and supported the attachment, proliferation of osteoblast (Saos-2) cells. Thus, the development of a non-toxic chemical cross-linking system with HPMC was investigated to fabricate K/HA/HPMC scaffold and our results showed great potential of these scaffolds to regenerate alveolar bone due to their structural similarity and excellent in vitro biocompatibility.